A Comparison of Isotoxic Dose-escalated Radiotherapy in Lung Cancer with Moderate Deep Inspiration Breath Hold, Mid-ventilation and Internal Target Volume Techniques. Issue 3 (March 2022) - Bainbridge, H.; Dunlop, A.; McQuaid, D.; Gulliford, S.; Gunapala, R.; Ahmed, M.; Locke, I.; Nill, S.; Oelfke, U.; McDonald, F.
Abstract: Aims: With interest in normal tissue sparing and dose-escalated radiotherapy in the treatment of inoperable locally advanced non-small cell lung cancer, this study investigated the impact of motion-managed moderate deep inspiration breath hold (mDIBH) on normal tissue sparing and dose-escalation potential and compared this to planning with a four-dimensional motion-encompassing internal target volume or motion-compensating mid-ventilation approach. Materials and methods: Twenty-one patients underwent four-dimensional and mDIBH planning computed tomography scans. Internal and mid-ventilation target volumes were generated on the four-dimensional scan, with mDIBH target volumes generated on the mDIBH scan. Isotoxic target dose-escalation guidelines were used to generate six plans per patient: three with a target dose cap and three without. Target dose-escalation potential, normal tissue complication probability and differences in pre-specified dose-volume metrics were evaluated for the three motion-management techniques. Results: The mean total lung volume was significantly greater with mDIBH compared with four-dimensional scans. Lung dose (mean and V21 Gy ) and mean heart dose were significantly reduced with mDIBH in comparison with four-dimensional-based approaches, and this translated to a significant reduction in heart and lung normal tissue complication probability with mDIBH. In 20/21 patients, the trial target prescription dose cap of 79.2 Gy was achievable with all motion-management techniques. Conclusion: mDIBH aids lung and heart dose sparing in isotoxic dose-escalated radiotherapy compared with four-dimensional planning techniques. Given concerns about lung and cardiac toxicity, particularly in an era of consolidation immunotherapy, reduced normal tissue doses may be advantageous for treatment tolerance and outcome. Highlights: mDIBH significantly increases lung volumes compared with 4DCT for lung radiotherapy. Heart and lung dose is significantly lower with mDIBH compared with 4DCT techniques. More than 20% reduction in modelled pneumonitis risk is seen with mDIBH versus 4DCT. mDIBH may be particularly beneficial in patients receiving adjuvant immunotherapy. mDIBH warrants further assessment, ideally within a randomised clinical trial.